MENINGKATKAN KETRAMPILAN TEKNIK DASAR PASSING SEPAKBOLA MELALUI PENGEMBANGAN MODEL BELAJAR PERMAINAN PADA SISWA PUTRA KELAS V SD - Pahala Tua Hutajulu (JURNAL OLAHRAGA PAPUA, 2013)
Abstract. Research and Development method has been performed to produce a new instructional model on passing skill games performance of V grade male elementary school students. Research and Development was carried out to analyze students’ need assessment and to examine product affectivity during teaching-learning process. The subjects of the research were 30 V grade male students from Kemayoran 04 Public Elementary School - Jakarta.Research and Development has been applied and data has been analyzed, yield some conclusion: (1) the new instructional model on passing skill games performance could improve student’s basic passing skill, (2) with the new instructional model, students showed more active contribution and enthusiasm during teaching-learning process, (3) teachers have several game models for learning basic skills of passing football.Keyword: instructional model games performance, passing skill, needs assessment, product.